Fatty liver indices in obese and non-obese patients with dyslipidemia - Peličić, Milena; Petrović, Milica; Popović, Ljiljana (Medicinski podmladak, 2024)
Introduction: The obesity pandemic is closely related to the growing prevalence and severity of fatty liver. Metabolic imbalances – insulin resistance and dyslipidemia – are cited as the main factors that create the basis for its occurrence and progression to non-alcoholic fatty liver disease (NAFLD), non-alcoholic steatohepatitis (NASH) and other complications (cirrhosis, hepatocellular carcinoma).Aim: The aim of the study was to compare the FLI and TyG indices within two groups of patients, obese and non - obese, as well as to determine their interrelationship and correlation with other laboratory parameters.Material and methods: The study included 62 patients, divided into two groups: obese and non-obese, equally represented (50%; 31). Anthropometric measurements and all laboratory tests of blood samples taken after 12 – 14 hours of night fasting were performed at the Clinic for Endocrinology, Diabetes and Metabolic Diseases UCCS. The FLI and TyG indices were calculated using appropriate algorithmic calculators.Results: The median of FLI in the obese patients was 86.4 and in the non-obese 13.7 (p
Keywords: obesity; FLI; TyG; NAFLD